Reducing Colorectal Cancer Incidence and Disparities: Performance and Outcomes of a Screening Colonoscopy Program in South Carolina. (23rd June 2014) - Xirasagar, Sudha; Li, Yi-Jhen; Burch, James B.; Daguisé, Virginie G.; Hurley, Thomas G.; Hébert, James R.
Abstract : This study evaluated the efficiency, effectiveness, and racial disparities reduction potential of Screening Colonoscopies for People Everywhere in South Carolina (SCOPE SC), a state-funded program for indigent persons aged 50–64 years (45–64 years for African American (AA)) with a medical home in community health centers. Patients were referred to existing referral network providers, and the centers were compensated for patient navigation. Data on procedures and patient demographics were analyzed. Of 782 individuals recruited (71.2% AA), 85% (665) completed the procedure (71.1% AA). The adenoma detection rate was 27.8% (males 34.6% and females 25.1%), advanced neoplasm rate 7.7% (including 3 cancers), cecum intubation rate 98.9%, inadequate bowel preparation rate 7.9%, and adverse event rate 0.9%. All indicators met the national quality benchmarks. The adenoma rate of 26.0% among AAs aged 45–49 years was similar to that of older Whites and AAs. We found that patient navigation and a medical home setting resulted in a successful and high-quality screening program. The observed high adenoma rate among younger AAs calls for more research with larger cohorts to evaluate the appropriateness of the current screening guidelines for AAs, given that they suffer 47% higher colorectal cancer mortality than Whites.